Efektivitas Pendekatan Kontekstual dalam Pembelajaran Bahasa Indonesia pada Siswa Sekolah Dasar: Kajian Literatur Empiris - Aini, Saripah; Rahmadani, Rosa; Zahara, Rizka; Apfani, Sry (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study examines the effectiveness of the Contextual Teaching and Learning (CTL) approach in Indonesian language learning at the elementary school level. The primary objective of this study is to explore the extent to which CTL can improve students' learning outcomes, reading skills, and critical thinking skills. Data collection was conducted through a literature review of relevant scientific articles published within the last five years. Articles were systematically selected based on the criteria of thematic relevance, source quality, and focus on Indonesian language learning in elementary schools. The study results indicate that the implementation of CTL consistently has a positive impact on reading comprehension, learning activities, and the development of students' critical thinking skills. However, challenges such as time constraints, teacher preparedness, and a lack of digital resources hinder its implementation. Therefore, institutional support and ongoing teacher training are key to the success of this approach in the context of elementary education.